Microvascular Decompression for Trigeminal Neuralgia: Our Experiences at Bir Hospital - Sharma, Gopal R; Jha, Rajiv; Poudel, Prakash; Adhikari, Dhrub R; Bista, Prakash (Nepal Journal of Neuroscience, 2017)
Trigeminal neuralgia (TGN) is a very peculiar disease, mostly characterized by unilateral paroxysmal facial pain, often described by patient as ‘one of the worst pain in my life’. This condition is also known as ‘Tic Douloureus’. The annual incidence of TN is about 4.7/100000 population, male and female are equally affected. The diagnosis is usually made by history, clinical fi ndings and cranial imaging is required to rule out compressing vascular loop, organic lesions and Multiple Sclerosis (MS) at Trigeminal nerve (TN). Treatment of TGN ranged from medical to surgical intervention. Between September 2007 and April 2015, 20 patients underwent micro vascular decompression (MVD) of TN for TGN who were refractory to medical treatment at department of Neurosurgery, Bir Hospital. All decompressions were performed using operating microscope. Follow up period ranged from 22 months to 8 years.There were 9 males and 11 females and age ranged from 30-70 years. The neuralgic pain was localized on right side in 13 patients and left on 7 patients. Pain distribution was on V3 (mandibular branch) dermatome in 11, V2( Maxillary branch ) in 4, V2-3 in 2 and V1- 2-3 in 3 patients respectively. On intraoperative fi ndings TN was compressed by superior cerebellar artery ( SCA ) in 8, tumors in 4, unidentifi ed vessels in 3, veins in 2, anterior inferior cerebellar artery ( AICA ) in 1 and no cause was found in 2 patients. 7 patients suffered postoperative complications which included hyposthesia in 3, pseudomeningocele in 3 and meningitis in 1. There was no mortality in this series. 20 patients felt pain relief immediately after procedure and 1 patients came after 3 years with recurrent pain requiring second surgery. In conclusion, MVD for TGN in younger patients who are refractory to medical treatment is one of the best treatment options which is safe and long term pain relief is achieved in majority of cases.Nepal Journal of Neuroscience, Vol. 14, No. 2,  2017 Page:11-15